An environmentally sensitive zinc-selective two-photon NIR fluorescent turn-on probe and zinc sensing in stroke - Junfeng Wang; Qibing Liu; Yingbo Li; Yi Pang (Elsevier, 2024)
A two-photon near infrared (NIR) fluorescence turn-on sensor with high selectivity and sensitivity for Zn2+ detection has been developed. This sensor exhibits a large Stokes' shift (∼300 nm) and can be excited from 900 to 1000 nm, with an emission wavelength of ∼785 nm, making it ideal for imaging in biological tissues. The sensor's high selectivity for Zn2+ over other structurally similar cations, such as Cd2+, makes it a promising tool for monitoring zinc ion levels in biological systems. Given the high concentration of zinc in thrombi, this sensor could provide a useful tool for in vivo thrombus imaging.